2015
DOI: 10.1021/jacs.5b09711
|View full text |Cite|
|
Sign up to set email alerts
|

DNA-Mediated Cellular Delivery of Functional Enzymes

Abstract: We report a strategy for creating a new class of protein transfection materials composed of a functional protein core chemically modified with a dense shell of oligonucleotides. These materials retain the native structure and catalytic ability of the hydrolytic enzyme β-galactosidase, which serves as the protein core, despite the functionalization of its surface with ∼25 DNA strands. The covalent attachment of a shell of oligonucleotides to the surface of β-galactosidase enhances its cellular uptake of by up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
125
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(130 citation statements)
references
References 46 publications
0
125
0
Order By: Relevance
“…Brodin et al [63] (Figure 5f) showed that cellular delivery of β-galactosidase (β-gal) can be enhanced by coating it with a dense shell of oligonucleotides. The large homotetrameric enzyme was reacted with an excess of a thiol-reactive fluorophore (AF647 maleimide), affording a tetramer with fluorophore modifications (AF4-β-gal).…”
Section: Enzyme Containers and Carriersmentioning
confidence: 99%
See 2 more Smart Citations
“…Brodin et al [63] (Figure 5f) showed that cellular delivery of β-galactosidase (β-gal) can be enhanced by coating it with a dense shell of oligonucleotides. The large homotetrameric enzyme was reacted with an excess of a thiol-reactive fluorophore (AF647 maleimide), affording a tetramer with fluorophore modifications (AF4-β-gal).…”
Section: Enzyme Containers and Carriersmentioning
confidence: 99%
“…The closed box efficiently protects the assembled enzyme cascade pair from protease digestion [59]; ( c ) A DNA origami-based nanocarrier loaded with luciferase (LUC) enzymes. The enzyme activity can be tuned by coating the carrier with cationic polymers [60]; ( d ) A light-triggered release of proteins such as bovine serum albumin (BSA) from DNA origami container [61]; ( e ) A DNA cage that can trap and release an enzyme (HRP) through the temperature-controlled conformational changes [62]; ( f ) β-galactosidase (β-gal) can be coated by DNA strands for significantly enhanced cellular delivery [63]. A box with a lid in ( a ) is reproduced with permission from [56].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…15 Nevertheless, the efficiency of delivery of these traditional methods is still limited, 16 in particular for proteins of large size. 17,18 …”
mentioning
confidence: 99%
“…Rapid delivery of β -gal to the cytosol is a promising approach for efficient prodrug activation therapy in cancer cells, 32,33 yet the large size of this enzyme (464 kD) in its tetrameric form is an obstacle for cytosolic access. 18 We assessed whether the GIPA NPSC platform was capable of efficiently delivering β -gal into the cytosol in HeLa. The size of β -gal-GIPA NPSCs is 110 ± 50 nm when measured by dynamic light scattering (DLS; ESI, Fig.…”
mentioning
confidence: 99%